Diabetic kidney disease as an independent predictor of long-term adverse outcomes in patients with coronary artery disease and diabetic mellitus - Liu, Zhiyu; Jiang, Rui; Xu, Ruochen; Wang, Yunzhe; Lv, Yan; Su, Chang; Yu, Fengyi; Qin, Zhen; Tang, JunNan; Zhang, JinYing (Frontiers in Cardiovascular Medicine, 2024)
Background：Diabetic kidney disease (DKD) had been proposed as a contributor in the pathogenesis of coronary artery disease (CAD). However, the relationship of DKD and long-term adverse outcomes in CAD patients after percutaneous coronary intervention (PCI) was still undiscovered.A number of 892 CAD patients enrolled from January 2012 to December 2016. The patients were divided into two groups, DKD group (n = 341) and None DKD group (n = 551). The primary outcome was major adverse cardiac events (MACE) after PCI. The average follow-up time was 1897 ± 1276 days.Results: Baseline data showed that some factors were significantly different between the two groups, including age, BMI, female, hypertension, smoking, stroke history, heart failure, duration of DM, LDL, UACR, serum creatinine, hemoglobin, platelet, antiplatelet, beta blocker, statin, antihypertensive drugs, insulin (p all< 0.005). There were significant differences between the two groups in MACE, 40.3% vs. 52.2% (p = 0.001), and in cardiovascular death events and all cause death events, (5.6% vs. 20.5%, p < 0.001; and 4.4% vs. 13.5%, p < 0.001). In DKD group, the risk of MACE event was elevated to 141.9% (HR = 1.419, 95% CI: 1.164-1.730, p = 0.001) in Cox univariable regression analyses; after adjusting co-variables, Cox Multivariable regression analyses demonstrated that DKD was an independent predictor for MACE (HR = 1.291, 95% CI: 1.027-1.624, p = 0.029) in CAD patients after PCI, also in cardiovascular death events (HR = 2.148, 95% CI: 1.292-3.572, p = 0.003) and all cause death events (HR = 2.229, 95% CI: 1.325-3.749, p = 0.003).This study suggests that DKD is an independent and novel predictor of long-term adverse outcomes in CAD with DM patients who underwent PCI.